Protein Palmitoylation and Pathogenesis in Apicomplexan Parasites - Corvi, María Martha (2012)
Apicomplexan parasites comprise a broad variety of protozoan parasites, including Toxoplasma gondii, Plasmodium, Eimeria, and Cryptosporidium species. Being intracellular parasites, the success in establishing pathogenesis relies in their ability to infect a hostcell and replicate within it. Protein palmitoylation is known to affect many aspects of cell biology. Furthermore, palmitoylation has recently been shown to affect important processes in T. gondii such as replication, invasion, and gliding. Thus, this paper focuses on the importance of protein palmitoylation in the pathogenesis of apicomplexan parasites.